Design and development of visitor management system - Oktaviandri, Muchamad; Kah, Keat Foong (Penerbit UMP, 2019)
This paper is mainly discussed about the design and develop the Visitor Management System (VMS) as an application that utilised the smart card advantages in University Malaysia Pahang (UMP) Pekan campus. This application is mainly focused on achieving an affordable VMS in UMP Pekan which aim to improve the existing visitor registration and information management activities. In fact, VMS replaces the manual recording of visitor information during visitor registration by using visitor’s Malaysia Government Multipurpose Card (MyKad). The VMS allows retrieving visitor information from MyKad and given a badge which use to indicate their identity when they are new registration visitor. From this study, it shows that the percentage of improvement for new visitor by using VMS is 26% to 54% higher compared to manual recording method whereas the percentage of improvement for existing visitor by using VMS is 86% to 91%. Further research of this study included the implementation on biometric verification method such as fingerprint and face recognition, replaces the current MyKad reader to smart card device with higher reading speed, as well as the notification system to inform the arrival of visitor to the visiting person.